2021
DOI: 10.1016/j.phymed.2021.153758
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Curcumin on multi-level immune checkpoint blockade and T cell dysfunction in head and neck cancer

Abstract: BackgroundDespite recent advances in understanding the complex immunologic dysfunction in the tumor microenvironment (TME), fewer than 20% of patients with head and neck squamous cell carcinoma (HNSCC) respond to immune checkpoint blockade (ICB). Thus, it is important to understand how inhibitory IC receptors maintain the suppressed dysfunctional TME, and to develop more effective combination immunotherapy. This study evaluated the immune-modulating effects of Curcumin, which has well-established anti-cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…Moreover, curcumin suppressed ovarian cancer growth in xenograft models by up-regulating circ-PLEKHM3 [ 86 ]. Curcumin could also reduce a transformative phenotype and tumor formation in the 4-nitroquinoline-1-oxide-induced head and neck cancer model, and tumor volume was significantly reduced after curcumin treatment [ 63 ]. Another study found that curcumin significantly reduced tumor weight and tumor size in BALB/c nude mice with SGC-7901 gastric cancer cells’ subcutaneous xenografts by promoting miR-34a expression [ 68 ].…”
Section: Effects and Mechanisms Of Curcumin On Cancersmentioning
confidence: 99%
“…Moreover, curcumin suppressed ovarian cancer growth in xenograft models by up-regulating circ-PLEKHM3 [ 86 ]. Curcumin could also reduce a transformative phenotype and tumor formation in the 4-nitroquinoline-1-oxide-induced head and neck cancer model, and tumor volume was significantly reduced after curcumin treatment [ 63 ]. Another study found that curcumin significantly reduced tumor weight and tumor size in BALB/c nude mice with SGC-7901 gastric cancer cells’ subcutaneous xenografts by promoting miR-34a expression [ 68 ].…”
Section: Effects and Mechanisms Of Curcumin On Cancersmentioning
confidence: 99%
“… 19 Increased CD8 + cytotoxic T cells and suppressed Treg activity as triggered by curcumin was reported to be associated with halted head and neck cancer cell invasion. 20 On the contrary, decreased CD8 + T cell density coupled with elevated Treg TME infiltration resulted in impaired IFNγ release from TILs and consequently a suppressive T cell contexture and accelerated colorectal cancer progression. 21 Accordingly, low CD8 + T cell and high Treg density was suggested as an useful index prognostic of poor lung adenocarcinoma outcome, alone or coupled with other biomarkers.…”
Section: Primary Cells In Tme and Their Roles In Cancermentioning
confidence: 99%
“…Thus, targeting immunosuppressive CD4 + T regulatory cells and rescuing CD8 + cytotoxic effector T cells is known to be a successful approach to enhance anti-tumor immunity and regression of tumor growth and metastasis. Various immunomodulatory drugs and molecules have been developed to enhance anti-tumor immune response but all of them have limitations due to their off-targeting effects or toxicity (15)(16)(17). Accumulating evidence suggests that chronic exposure of UV radiation induces an immunosuppressive tumor microenvironment in skin tumor via diminishing antigen-presenting cell function, increasing production of immunosuppressive cytokines, and modulating contact and delayed type of hypersensitivity during skin carcinogenesis (18).…”
Section: Commentarymentioning
confidence: 99%